Video and Theatre or a Hybrid Scene: The Case of Theatrical Mise En Scène Fanny and Alexander - Miloš Mistrík, (Communication Today, 2025)
Today’s theatrical art sometimes utilizes modern electronic technologies of visualisation that may be, especially if we use a certain amount of simplification, generally defined as “video”. This kind of technology consists of a complex set of devices: shooting cameras, recording devices, trick equipment, broadcasting devices, screens. Theatrical mise en scènes once used to involve film; however, mostly before the emergence and refinement of digital video technologies. It is beyond any doubts that compared to film, video has many advantages – one of the most significant of these advantages is the fact that video technology allows to provide simultaneous online streaming of both image and sound. In case creators and producers of a theatrical mise en scène decide to use such a technology, they tend to favour it over the theatrical elements, which may lead to a shift from mimesis towards virtualisation of the performed spectacle. On the other hand, classic theatre, along with its long-term tradition and solid forms, is a strong, persistent sphere of art; even the video is rarely able to prevail and change the scenic reality into a virtual, abstract electronic world. We have decided to discuss these theoretical notions in relation to the theatrical mise en scène Fanny and Alexander by Ingmar Bergman, which was directed by Marián Amsler and performed at the Slovak National Theatre in 2016. Our analysis reflects on the forms of hybrid convergence merging theatrical art and video art in this particular case. However, as the conclusion suggests, video art and its technological possibilities may have influenced the mise en scène’s overall setting, but the given theatrical work was able to preserve its own integrity without sacrificing any part of the true nature of theatre as such.